Synthesis of Substituted Benzimidazoles and Imidazo[4,5-b]pyridines Under Microwave and Solvent-free Conditions - Montazeri, Nasser; Rad-Moghadam, Kurosh (Asian Journal of Chemistry, 2010)
A clean and facile synthesis of benzimidazoles and imidazo[4,5-b]pyridines is achieved from cyclocondensation of 1,2-diaminoaromatics with o-esters catalyzed by SiO2/H2SO4 in dry and microwave conditions.